FAKTOR PENYEBAB RENDAHNYA NILAI SOSIOLOGI SISWA DI SMA NEGERI I BONJOL KECAMATAN BONJOL KABUPATEN PASAMAN - Zulfitri, Linda; Maihasni, Maihasni; Elvawati, Elvawati (Pendidikan Sosiologi, 2013)
In  this  reseach,  the  reseacher  used  structuration  Giddens  theory,  with internal and external factor to compel the people to do something. The approach used in this research was qualitative method with descriptive type to describe the detail in research.In  colecting  the  data,  the  reseacher  used  observation  and  interview.  The informant of the research with purposive sampling. The unit of the data analysis was people, with some stap. Collecting the data, reduction the data or analyzing the data, verification and conclusion.Based on the result of the research, the cause of lower score of sociology students in Senior High School I Bonjol was internal and external factor. Internal factor  like:  1)  lack  of  students  attention  in  learning  process,  2)  lack  of  students motivation  in  learning  process,  3)  lack  of  students  readness  in  learning  processmain while, external factor sich as: 1) lack of parents participation, 2) lack of clear rule, 3) lack of facilities and infrastructure, 4) teacher method not interesting.